Do government linked companies hold more cash? - LIU, Chenxi (Institutional Knowledge at Singapore Management University, 2016)
In this paper, we investigate the cash holings of government linked corporations (GLCs) in Singapore, with different levels of Temasek Holdings ownership. We find evidence that Temasek owned public firms hold on average substantially more cash than otherwise similar public firms listed on SGX. This result is robust to different measures of Temasek ownership. We also show that when GLCs have excess cash, they do not spend it on capital expenditure, acquisition, dividends or share repurchase. Instead, they hoard these excess cash leading to an accumulation of cash. In addition, we show that Temasek firms are on average more profitable, however the accumulation of excess cash is reducing their profitability.